Cover Jurnal Media Teknik Sipil Vol.12, No.2 Agustus 2014 - Cover . (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2014)
Cover Jurnal Media Teknik Sipil Vol.12, No.2 Agustus 2014